2008
DOI: 10.1534/genetics.107.073346
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Mitochondrial Genetic Diversity in Mammals

Abstract: Mitochondrial DNA (mtDNA) is one of the most popular population genetic markers. Its relevance as an indicator of population size and history has recently been questioned by several large-scale studies in animals reporting evidence for recurrent adaptive evolution, at least in invertebrates. Here we focus on mammals, a more restricted taxonomic group for which the issue of mtDNA near neutrality is crucial. By analyzing the distribution of mtDNA diversity across species and relating it to allozyme diversity, li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
140
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(150 citation statements)
references
References 67 publications
8
140
2
Order By: Relevance
“…Previous work has found that selection on mtDNA makes it a poor indicator of population size (Bazin et al 2006;Nabholz et al 2009) or species history (Bensch et al 2006) or is uncorrelated with life history traits (Nabholz et al 2008), but other work suggests that selection is not strong enough to bias phylogenetic inference (Zink 2005). Our results that mtDNA was under weak positive selection differ from previous work showing purifying selection reduced mtDNA genetic variability (Bazin et al 2006;Stewart et al 2008), but evidence of positive selection on mtDNA is not a unique finding.…”
Section: Selection On Mtdnacontrasting
confidence: 88%
See 1 more Smart Citation
“…Previous work has found that selection on mtDNA makes it a poor indicator of population size (Bazin et al 2006;Nabholz et al 2009) or species history (Bensch et al 2006) or is uncorrelated with life history traits (Nabholz et al 2008), but other work suggests that selection is not strong enough to bias phylogenetic inference (Zink 2005). Our results that mtDNA was under weak positive selection differ from previous work showing purifying selection reduced mtDNA genetic variability (Bazin et al 2006;Stewart et al 2008), but evidence of positive selection on mtDNA is not a unique finding.…”
Section: Selection On Mtdnacontrasting
confidence: 88%
“…However, mtDNA and nuclear DNA can exhibit discordant phylogeographic patterns due to sex-biased dispersal (Peters et al 2012), introgression (Bryson et al 2010;Reid et al 2012), and/or incomplete lineage sorting (Ballard and Whitlock 2004). Further, the utility of mtDNA as a phylogenetic marker has been questioned because of evidence of selective sweeps causing mtDNA genetic diversity to be incongruent with species abundance estimates (Bazin et al 2006;Nabholz et al 2008Nabholz et al , 2009. Since phylogeographic studies often do not measure selection, the usage of PRF models to estimate divergence times, effective population sizes, and selection coefficients provides a means of incorporating the informativeness of mtDNA and at the same time assessing the strength of selection on mtDNA markers.…”
mentioning
confidence: 99%
“…Conversely, Bazin et al (2006) reported a non-significantly negative correlation (Kendall t¼À0.14) between mtDNA sequence diversity and nuclear allozyme genetic diversity across eight major animal groups encompassing 1683 species, while finding a significant positive correlation between nuclear DNA diversity and allozyme diversity (t¼0.87) across the same groups. Subsequent analyses using the same data set revealed significant positive correlations between mtDNA and allozyme genetic diversity across eutherian mammalian orders (Mulligan et al, 2006) and within mammals (Nabholz et al, 2008b). Several other studies have also reported positive correlations between mtDNA diversity and population size or its surrogates (Table 1), but these have all involved data across a narrower taxonomic range than used by Bazin et al (2006).…”
Section: Correlations Of Genetic Diversity With Population Size and Fmentioning
confidence: 79%
“…They suggested that complete genetic linkage in mtDNA genomes and recurrent positive selection (Gillespie 2001) may underlie such patterns. However, within-taxa comparisons show positive correlations between mtDNA heterozygosity and nuclear genome variation in mammals (Mulligan et al 2006;Nabholz et al 2008) and other animals (Piganeau and Eyre-Walker 2009). Variation in mutation rates, adaptive evolution, and=or biased transmission may contribute to within-and between-taxa differences for mtDNA polymorphism.…”
mentioning
confidence: 99%